EVALUATION OF PORTABLE ULTRASOUND TECHNOLOGY AND THE CORRELATION WITH THE FAT PERCENTAGE THROUGH SKINFOLDS IN YOUNG ADULTS - Krueger, Eddy; Ulbricht, Leandra; Ripka, Wagner; Neves, Eduardo Borba (Journal of Health Care, 2015)
Introduction: The aim of this study was to compare and correlate the results of fat percentage by skinfold thickness using portable ultrasound (US) and scientific adipometer in adults. Methods: During2012 we evaluated 120 military men, divided according to the value of the body mass index (BMI). Wecollected: weight, height, SF and US in nine points (triceps, subscapular, biceps, chest, medium axillary,abdominal, supra iliac, anterior thigh and calf ). Statistical analysis was performed using nonparametrictests as Spearman correlation coefficient and paired with Wilcoxon Signed Ranks Test. Results:For the correlation of the percentage of fat obtained through seven skinfolds and values obtained bymeasuring it with US, the following results were obtained: p=0.421 (BMI<25 kg/mÂ², N= 94); p=0.419(BMI=25 kg/mÂ², N=26); p=0.514 (general BMI, N=120), where all correlations were statistically significant(p<0.05). Points with the highest correlations were the thigh (p=0.65) and triceps (p=0.63). Conclusion: Comparing the percentage of fat estimated between portable ultrasound and adipometer,there were significant correlations between all points assessed, but with lower US values than skin foldthickness at every point analyzed (except for the biceps brachialis). We recommend that future studiesshould be carried out comparing portable US with Dual-energy X-ray absorptiometry, so we could effectively verify if there is a correlation between the diagnoses obtained from this new technology witha gold standard technique.